Modernism and Popular Music - Schleifer, Ronald (Cambridge Cambridge University Press, 2011)
"Traditionally, ideas about twentieth-century 'modernism' - whether focused on literature, music or the visual arts - have made a distinction between 'high' art and the 'popular' arts of best-selling fiction, jazz and other forms of popular music, and commercial art of one form or another. In Modernism and Popular Music, Ronald Schleifer instead shows how the music of George and Ira Gershwin, Cole Porter, Thomas 'Fats' Waller and Billie Holiday can be considered as artistic expressions equal to those of the traditional high art practices in music and literature. Combining detailed attention to the language and aesthetics of popular music with an examination of its early twentieth-century performance and dissemination through the new technologies of the radio and phonograph, Schleifer explores the 'popularity' of popular music in order to reconsider received and seeming self-evident truths about the differences between high art and popular art and, indeed, about twentieth-century modernism altogether" -- Provided by publisher.
Machine generated contents note: Preface; Introduction: popular music and the experience of modernism; Part I. Musical Modernism: Popular Music in the Time of Jazz: 1. Classical modernity and popular music; 2. Twentieth-century modernism and 'jazz' music; Part II. Gershwin, Porter, Waller, and Holiday: 3. Melting pot and meeting place: the Gershwin brothers and the arts of quotation; 4. 'What is this thing called love?': Cole Porter and the rhythms of desire; 5. Signifying music: Fats Waller and the time of jazz; 6. Music without composition: Billie Holiday and ensemble performance; Postscript: popular music and the revolution of the word; Bibliography; Index.
Electronicreproduction.
Keywords: Modernism (Music); Popular music -- History and criticism. -- United States; Jazz -- History and criticism